Perturbations in inter-domain associations may trigger the onset of pathogenic transformations in PrPC: insights from atomistic simulations - Menon, Sneha; Sengupta, Neelanjana (Molecular Biosystems, 2015)
Conversion of the predominantly alpha-helical cellular prion protein (PrPC) to the misfolded beta-sheet enriched Scrapie form (PrPSc) is a critical event in prion pathogenesis. However, the conformational triggers that lead to the isoform conversion (PrPC to PrPSc) remain obscure, and conjectures about the role of unusually hydrophilic, short helix H1 of the C-terminal globular domain in the transition are varied. Helix H1 is anchored to helix H3 via a few stabilizing polar interactions. We have employed fully atomistic molecular dynamics simulations to study the effects triggered by a minor perturbation in the network of these non-bonded interactions in PrPC. The elimination of just one of the key H1-H3 hydrogen bonds led to a cascade of conformational changes that are consistent with those observed in partially unfolded intermediates of PrPC, with pathogenic mutations and in low pH environments. Our analyses reveal that the perturbation results in the enhanced conformational flexibility of the protein. The resultant enhancement in the dynamics leads to overall increased solvent exposure of the hydrophobic core residues and concomitant disruption of the H1-H3 inter-domain salt bridge network. This study lends credence to the hypothesis that perturbing the cooperativity of the stabilizing interactions in the PrPC globular domain can critically affect its dynamics and may lead to structural transitions of pathological relevance.

Influence of hyperglycemic conditions on self-association of the alzheimer's amyloid beta (a beta(1-42)) peptide - Menon, Sneha; Sengupta, Neelanjana (ACS Omega, 2017)
<div id="absImg" style="position: relative; margin: 0px; padding: 5px; border: 1px solid rgb(204, 204, 204); border-radius: 5px; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial; text-align: center; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;"><img alt="Abstract Image" src="http://pubs.acs.org/appl/literatum/publisher/achs/journals/content/acsodf/2017/acsodf.2017.2.issue-5/acsomega.7b00018/20170517/images/medium/ao-2017-00018p_0003.gif" style="border: 0px; max-width: 100%;"> <p class="articleBody_abstractText" style="margin: 0px 0px 1.5em; line-height: 1.6em; padding: 0pt; width: 610px; word-wrap: break-word; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;">Clinical studies have identified a correlation between type-2 diabetes mellitus and cognitive decrements en route to the onset of Alzheimer’s disease (AD). Recent studies have established that post-translational modifications of the amyloid β (Aβ) peptide occur under hyperglycemic conditions; particularly, the process of glycation exacerbates its neurotoxicity and accelerates AD progression. In view of the assertion that macromolecular crowding has an altering effect on protein self-assembly, it is crucial to characterize the effects of hyperglycemic conditions via crowding on Aβ self-assembly. Toward this purpose, fully atomistic molecular dynamics simulations were performed to study the effects of glucose crowding on Aβ dimerization, which is the smallest known neurotoxic species. The dimers formed in the glucose-crowded environment were found to have weaker associations as compared to that of those formed in water. Binding free energy calculations show that the reduced binding strength of the dimers can be mainly attributed to the overall weakening of the dispersion interactions correlated with substantial loss of interpeptide contacts in the hydrophobic patches of the Aβ units. Analysis to discern the differential solvation pattern in the glucose-crowded and pure water systems revealed that glucose molecules cluster around the protein, at a distance of 5–7 Å, which traps the water molecules in close association with the protein surface. This preferential exclusion of glucose molecules and resulting hydration of the Aβ peptides has a screening effect on the hydrophobic interactions, which in turn diminishes the binding strength of the resulting dimers. Our results imply that physical effects attributed to crowded hyperglycemic environments are incapable of solely promoting Aβ self-assembly, indicating that further mechanistic studies are required to provide insights into the self-assembly of post-translationally modified Aβ peptides, known to possess aggravated toxicity, under these conditions.
Keywords: Conformation; Drug discovery and Drug delivery systems; Free energy; Glycoproteins; Molecular association; Molecular dynamics simulation

Effect of hyperglycemic conditions on the early self-assembly of the alzheimer's amyloid beta peptide: implications for neurotoxicity - Menon, Sneha; Sengupta, Neelanjana (Biophysical Journal, 2018)

Cold thermal response of an amyloid oligomer differs from typical globular protein cold denaturation - Menon, Sneha; Sengupta, Neelanjana (Journal of Physical Chemistry Letters, 2019)
In contrast with the general behavior of folded proteins, the cold thermal response of amyloid assemblies is difficult to elicit with simple models. We exploit exhaustive simulations to evaluate the thermal response of a barrel-shaped model amyloid oligomer, with a distinct hydrophobic core akin to that of folded proteins. Cumulative thermal data over the range of 210-483 K indicate a sharp inflection and rise in structural stability as the temperature is decreased below the melting temperature of the water model. This is not commensurate with the equilibrium free energy profile obtained with core packing as the order parameter. However, energetic analyses and the size of their fluctuations indicate the crucial role of hydration in mediating structural transitions, beyond the expected temperature-dependent hydrophobic effect. Structural ordering of the hydration layer over bulk water is maximized at the transition and vanishes at high temperatures. This is a first direct demonstration of the microscopic influence of hydration water on the low-temperature response of an amyloid assembly close to the cryo-regime.

Influence of crowding and surfaces on protein amyloidogenesis: A thermo-kinetic perspective - Menon, Sneha; Sengupta, Neelanjana (Biochimica ET Biophysica Acta-Proteins and Proteomics, 2019)
The last few decades have irreversibly implicated protein self-assembly and aggregation leading to amyloid fibril formation in proteopathies that include several neurodegenerative diseases. Emerging studies recognize the importance of eliciting the pathways leading to protein aggregation in the context of the crowded intracellular environment rather than in conventional in vitro conditions. It is found that crowded environments can have acceleratory as well as inhibitory effects on protein aggregation, depending on the interplay of underlying factors on the crucial rate limiting steps. The aggregation mechanism and transient species formed along the pathway are further altered when they interface with natural and artificial surfaces in the cellular milieu. An increasing number of studies probe the autocatalytic nature of amyloid surfaces as well as membrane bilayer effects on amyloidogenesis. Moreover, exposure to modern nanosurfaces via nanomedicines and other sources potentially invokes beneficial or deleterious biological response that needs rigorous investigation. Mounting evidences indicate that nanoparticles can either promote or impede amyloid aggregation, spurring efforts to tune their interactions for developing effective anti-amyloid strategies. Mechanistic insights into nanoparticle mediated aggregation pathways are therefore crucial for engineering anti-amyloid nanoparticle strategies that are biocompatible and sustainable. This review is a compilation of studies that contribute to the current understanding of the altering effects of molecular crowding as well as natural and artificial surfaces on protein amyloidogenesis.

Nanoscale interplay of membrane composition and amyloid self-assembly - Menon, Sneha; Sengupta, Neelanjana; Das, Payel (Journal of Physical Chemistry B, 2020)
Cell membranes are complex assemblies of lipids and proteins exhibiting lipid compositional heterogeneity between the inner and outer leaflets of the bilayer. Aberrant protein aggregation, implicated in a number of neurodegenerative diseases including Alzheimer's, is known to result in both extracellular and intracellular deposits with divergent pathophysiological effects. Mounting evidence substantiates membrane-mediated amyloid effects and indicates membrane composition, particularly gangliosides, as a plausible factor influencing the fibrillation process. By employing exhaustive molecular dynamics simulations using a coarse-grained model, we probed the assembly behavior of amyloidogenic A beta(12-28) peptides on the chemically heterogeneous extracellular (outer) and cytosolic (inner) leaflets of a mammalian plasma membrane. Our results indicate that the compositional nature of the membrane has a crucial impact on the peptide self-assembly. Peptide oligomerization is hindered on the outer leaflet relative to the inner leaflet due to a competition between interpeptide and peptide-membrane interactions, resulting in higher population of smaller oligomers. The weaker associations among peptides on the outer membrane can be attributed to the favorable interactions of the peptides with gangliosides (GM) that characterize the extracellular membrane. At a higher peptide:GM ratio, we observe enhanced nanoclustering of GM lipids mediated by preferential GM-A beta binding. Interaction between peptide and GM further impacts local membrane curvature; there is a concomitant loss in membrane concavity due to looser GM packing. Our simulations provide molecular insights into the role of membrane composition on A beta aggregation and lend credence to earlier reports of ganglioside-mediated A beta aggregation in the outer membrane. We also demonstrate the effects of local peptide assemblies on the membrane structure and dynamics.